Assessment of Rational Use of Antibiotics in a Private Tertiary Care Teaching Hospital - Rajalingam, B.; Alex, Achsah Susan; Godwin, Adreen; Cherian, Chinnu; Cyriac, Clincy (Indian Journal of Pharmacy Practice)
Introduction: Rational use of antibiotics is important, as antibiotic resistance is not only a problem for the individual patient but also reduces effectiveness of established treatment and has become a major threat to public health by increasing complexity, cost of treatment and reducing the probability of successful outcome. Objectives: To compare the treatment of different diseases with standard clinical guidelines by implementing indicators for antibiotic usage. Methods: 200 patients were enrolled in a 6 month prospective randomised study as per the inclusion and exclusion criteria. Results: A total of 1955 general drugs were prescribed to patients with an average of 9.09 ± 6.95 drugs. The average length of stay for study population was found to be 7.5 ± 4.18 days. The rationality was assessed using guidelines prepared from Micromedex and NFI 2011. The most commonly prescribed antibiotics were Ceftriaxone (15.38%) and Levofloxacin (6.76%). The most commonly prescribed FDC were Cefepime+Tazobactum (19.69%) and Piperacillin+Tazobactum (14.76%). Sensitivity tests were done for 37 patients and was found that Cefepime/Tazobactum were more sensitive to S. pneumoniae followed by gram positive cocci and Amikacin to be more sensitive to E.coli. When rationality was checked for the overall appropriateness of antibiotics, it was found to be 57.85%. Appropriateness of antibiotics was checked for indication (60.61%), duration (55.38%), dose (59.07%) and frequency (56.31%). The average interaction per prescription was found to be 1.5 ± 1.29. Out of 205 incompatibilities 60.97% were with antibiotics. Conclusion: There is a vital need for microbiological investigation before treatment of infections. This study should help physicians to have better insight about prescription patterns.
Keywords: Rationality; Antibiotics; Micromedex; Drug Interactions; IV incompatibility